A Quasy Experimental Study: Buku Saku Cegah Anemia Remaja (Care) Efektif Meningkatkan Pengetahuan dan Sikap Remaja Putri tentang Anemia - Rosa Mesalina; Siti Khadijah; Sania Lailatu Rahmi; Lili Dariani; Yosi Sefrina (Jurnal Sehat Mandiri, 2026)
Anemia in adolescent girls remains a public health problem that has a long-term impact on reproductive health and the risk of stunting in the next generation. Low knowledge and attitudes among adolescents towards anemia are important factors that contribute to suboptimal preventive behavior. Education through simple, practical, and easy-to-understand such as pocket books has the potential to be an effective promotive-preventive intervention. This study aims to analyze the effectiveness of using the Cegah Anemia Remaja (CARE) pocketbook in increasing adolescent girls' knowledge and attitudes about anemia. This study used a quasi-experimental two-group pre-post design, with sample consisted of female adolescents pursuing higher education. The intervention used CARE pocketbook, was given to the experimental group, while the control group received random educational media. Knowledge and attitude measurements were conducted before and after the intervention. Data analysis used the Wilcoxon test and Mann–Whitney U. The results showed a significant increase in knowledge and attitudes in the experimental group after intervention. Between groups, the improvement in knowledge and attitudes among adolescent girls in the experimental group was significantly higher than in the control group. The CARE pocketbook proved to be effective in increasing adolescent girls' knowledge and attitudes about anemia. Contextually designed print educational media tailored to the characteristics of adolescents can be a strategic alternative in adolescent anemia prevention programs.